Traditional Indonesian carved ornaments in Rancakan contemporary gamelan to support fine arts learning - Hermanto, Bambang; Ponimin, Ponimin; Rahayuningtyas, Wida; Zulkifli, Norzizi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
The teaching process in the form of teaching, training and research can be a means to strengthen steps in living in the world so that achievements in the fields of knowledge and skills are expected by everyone, namely a way to fully enjoy life based on the world. These human needs and desires can be fulfilled by the emergence of creative thinking ideas and innovative thinking ideas which are achieved by studying one's education. The aim of this research is to increase students' love for Indonesian culture through "Nusantara Ornaments". The design of this research is qualitative research. The population and sample in this study consisted of MAN Batu students in class. The results of this research are that students can describe works of applied art through ana-lytical sketches which include application, installation and combination columns. We conclude that the activity of observing and carrying out art criticism can help students gain information about works of applied art, the artists who created them, and the pro-cess of creating sculpture according to the students themselves.